Analisis Terhadap Assesmen Minat dan Bakat dalam Perencanaan Karir Peserta Didik Kelas XII - Arlita, Monica; Herwantoro; Hartini; Sumarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of interest and talent assessments in the career planning of 12th-grade students. The method used is library research with reference to the PRISMA 2020 guidelines. Data were obtained from various scientific literature sources published during the period 2020–2025 through the databases Google Scholar, ERIC, ResearchGate, DOAJ, and Garuda. The selected literature was analyzed using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The review of 14 pieces of literature showed that interest and talent assessments significantly contribute to helping students understand their personal potential, enhance career maturity, strengthen career self-efficacy, and support more accurate educational and occupational decision-making. Interest assessment plays a role in identifying students' tendency to be interested in certain fields, while talent assessment helps. Interest assessment plays a role in identifying students' tendencies to be interested in certain fields, while talent assessment helps reveal the abilities and potential they possess. Research findings also indicate that the effectiveness of assessments is influenced by the role of guidance and counseling teachers in interpreting assessment results and integrating them into career guidance services. Thus, interest and talent assessments are an important foundation in students' career planning and need to be optimized through systematic and continuous guidance and counseling services in schools.